Forward guidance, quantitative easing, or both? - Ferre De Graeve; Konstantinos Theodoridis (National Bank of Belgium, 2016)
During the Great Recession numerous central banks have implemented various unconventional monetary policy measures. This paper aims to empirically evaluate two particular types of unconventional policies (forward guidance and quantitative easing) in a structural manner. The primary aim is to evaluate the policies jointly, to mitigate concerns that empirical evaluation of either policy in isolation is prone to at least partially absorb the effects of the other - typically simultaneously implemented - policy. The approach is structural to overcome inherent empirical difficulties in evaluating policies, e.g. in the wake of anticipation. The model is estimated for the US (1975-2015) and sheds light on the historical real effects of the government debt maturity structure as well as the contribution of Fed policy through its maturity policy during the crisis.
Keywords: E40; E43; E52; E58; E63; 330; Unconventional monetary policy; quantitative easing; forward guidance; Geldtheorie; Zentralbank; Geldpolitik; Quantitative Lockerung; Geldpolitische Transmission; Schätzung